ANXIETY DISORDERS AND DEPRESSION IN CHILDREN WITH FUNCTIONAL SOMATIC SYMPTOMS- A CASE-CONTROL STUDY FROM INDIA - Sreedevi P A; Suma Balan; Gitanjali Natarajan; Bhanu Vikraman Pillai; C Jayakumar; Sheejamol V. S (Universitas Airlangga, 2025)
Introduction: Nearly 10% of children and adolescents suffer from functional somatic symptoms (FSS) which are persistent, bothersome bodily symptoms not having demonstrable organic pathology. Associations have been reported between children’s FSS, anxiety, depression, and certain parental factors. Aims: (i) compare the anxiety and depression levels between children with FSS and children not having FSS, (ii) identify the child and parent-related risk factors of FSS. Methods: Case-control design was used for this cross-sectional study. Cases constituted a hospital sample of 60 children, aged 9-15 years, who presented with FSS. Age, gender and class-matched 60 school children, who did not disclose any FSS while screening with Children’s Somatic Symptoms Inventory-24 constituted the control group. Both the groups were administered with Revised Children’s Anxiety and Depression Scale, Illness Behaviour Encouragement Scale, and Lum Emotional Availability of Parents (Child report). Results: Cases scored significantly higher than the control children on anxiety, depression (p<0.001), and parental illness behaviour encouragement (p<0.001), but reported low emotional availability of both parents (p<0.01). Significantly large number of children in the FSS group showed anxiety disorder (p<0.05), separation anxiety disorder (p<0.001) generalized anxiety disorder (p<0.01), and major depressive disorder (p<0.01). The stepwise multiple logistic regression analysis revealed over all anxiety, separation anxiety, generalized anxiety and high parental illness encouragement as the risk factors of FSS. Conversely, higher perception of maternal emotional availability significantly reduced its risk. Conclusion: Children with FSS must be screened for anxiety and depressive disorders as well as parental reinforcing responses and emotional availability before initiating treatment.